Perfil metabólico energético em dois grupos genéticos de Vacas holandês x Gir de segunda ordem de parição, em dois períodos da lactação, na época da seca, nos trópicos - Penna Júnior, César Otaviano (2010)
The cross-breeding derived from specialized milk producing European breeds with zebu breeds that are adapted to tropical conditions form the basis of the majority of Brazil s milk producing systems. However, researches regarding the metabolic profile (MP) for bovine dairy cows focus on pure breeds coming mostly from temperate to subtropical regions. Therefore, the behaviour of the hematobiochemical components indicators on the energy metabolism in second calving rate order ½ and ¾ Holstein x Gir (HG) dairy cows, in two stages of lactation, became the object of the evaluation, as well as to determine its relationship with body condition (BCS) and milk production during the dry season in tropical environment. The experiment was conducted at Santa Luzia Farm, located in Minas Gerais - Brazil. This study used data collected in the months of May and August 2009 from 37 ½ HG cows and 35 ¾ HG cows. By our definition studies were focused on two lactation periods, the first being from 28 to 60 days (P1 lactation) and the second from 110 to130 days (P2 of lactation). The cows received complete feed in the trough. The biochemical indicators of the metabolic energy profile were analyzed through the beta-hydroxybutyrate (ßHB), cholesterol and the enzyme Aspartate transaminase (AST) quantifications. The metabolite average values, with their standard errors, analyzed by Student test, were established for both blood degrees, in their respective lactation periods. Given the scarcity of information on reference values for the genetic group investigated in this study, reference values were methodically sought from studies using larger number of variables equal to the present study. There were statistical differences between the periods for ßHB, milk production and BCS, whereas the other parameters did not differ for cows ½ and ¾ HG. There were statistical differences between the periods in ßHB, milk production and BCS, whereas the other parameters did not differ for ½ and ¾ HG cows. Between blood degrees, the statistical differences occurred within each period concerning the ßHB and milk production parameters and no other differences occurred in relation to the remaining parameters. Having obtained the results and taking the conditions to which the animals were exposed in this study into consideration, we have concluded that the genetic groups were effective in sustaining their respective levels of milk production without experiencing complications of metabolic order. We suggest such studies to be continuated as to equate Reference Values